Unravelling the underpinning mechanisms associated with the microwave treatment of electric arc furnace dust with polyvinyl chloride: an electromagnetic and kinetic investigation - Altarawneh, Sanad (2023)
Herein, the underpinning mechanisms associated with the microwave thermal treatment of electric arc furnace dust (EAFD) with polyvinyl chloride (PVC) in terms of their response to the electromagnetic radiation in the microwave frequency band and the effect of EAFD pure constituents on the thermal degradation kinetics of PVC have been studied. Such data provide a foundation based on which the co-thermal treatment of EAFD and PVC can be realised using microwave energy as an alternative disposal strategy for these wastes. The separation of the microwave electromagnetic fields was achieved in a TE10 cavity by means of using small cylindrical samples with a 4 mm diameter along with the correct positioning of the sliding short circuit such that the electric or magnetic field was solely passed through the sample. Heating experiments suggests that ZnO, ZnFe2O4, Fe3O4, and graphite are the major phases that contribute to the microwave heating of EAFD with ZnO having the highest heating rate (~ 37 °C/s) among zinc and iron bearing oxides. Moreover, only Fe3O4 and graphite heated in the magnetic field suggesting the possibility of selective heating of these phases by the microwave magnetic field maxima. The non-isothermal kinetic analysis performed on the thermogravimetric scans of metal oxides/PVC mixtures suggests a catalytic activity for both ZnO and ZnFe2O4 in which both were found to react directly with the PVC monomer resulting in a drop in the de-hydrochlorination onset temperature from 272 to 214 and 235 °C, respectively. The resulting products from this interaction is majorly zinc in its water soluble chloride form (ZnCl2) which suggests that PVC can be utilised as a potential additive for the recycling of metallurgical waste (e.g., EAFD). To provide a selective chlorination of zinc in ZnFe2O4 while leaving iron in its stable oxide form (Fe2O3), the pyrolysis should be performed at temperatures as low as 235 °C. This is because the presence of parallel reactions with different energy barriers results in reaction channelling favouring the chlorination of zinc while the resulting Fe2O3 remains untouched due to its slow reaction kinetics with H2 in that temperature range (i.e., iron remains as stable Fe2O3 instead of transforming to active Fe3O4). The reaction of Fe3O4 and Fe2O3 (after reduction to Fe3O4) with PVC was found to occur by reacting with gaseous emitted HCl, contrary to ZnO and ZnFe2O4 which react directly with the PVC monomer. The onset de-hydrochlorination temperature of PVC was thus not affected when PVC was mixed with Fe3O4 and Fe2O3. The capturing of the emitted gaseous HCl resulted, however, in slowing the rate of the de-hydrochlorination stage since HCl is a known catalyst for PVC de-hydrochlorination which was seen in the form of an increase in the activation energy associated with that stage. Combining the observations from both an electromagnetic and kinetic perspective, it is believed that utilising microwave energy can result in a fast selective heating of zinc bearing oxides over iron bearing compounds. This, in turn, would allow PVC in contact with ZnO and ZnFe2O4 to heat at a faster rate leading to channelling the chlorination reactions towards zinc oxides, which enhances the chlorinating selectivity, especially that all the chlorine will be abstracted by “high temperature” ZnO and ZnFe2O4 before PVC decomposes normally into gaseous HCl and solid polyene.